2019
DOI: 10.26493/1855-3974.1426.212
|View full text |Cite
|
Sign up to set email alerts
|

On the generalized Oberwolfach problem

Abstract: The generalized Oberwolfach problem OP t (2w + 1; N 1 , N 2 ,. .. , N t ; α 1 , α 2 ,. .. , α t) asks for a factorization of K 2w+1 into α i C Ni-factors (where a C Ni-factor of K 2w+1 is a spanning subgraph whose components are cycles of length N i ≥ 3) for i = 1, 2,. .. , t. Necessarily, N = lcm(N 1 , N 2 ,. .. , N t) is a divisor of 2w + 1 and w = t i=1 α i. For t = 1 we have the classic Oberwolfach problem. For t = 2 this is the well-studied Hamilton-Waterloo problem, whereas for t ≥ 3 very little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In this paper, we consider the case of m and n being of different parity. This case has gained attention recently, where it has been shown that the necessary conditions are sufficient for a (m, n)− HWP(v; r, s) whenever m | n, v > 6n > 36m, and s ≥ 3 [10]. We provide a complementary result to this in our main theorem, which covers cases in which m ∤ n and solves a major portion of the problem.…”
mentioning
confidence: 82%
“…In this paper, we consider the case of m and n being of different parity. This case has gained attention recently, where it has been shown that the necessary conditions are sufficient for a (m, n)− HWP(v; r, s) whenever m | n, v > 6n > 36m, and s ≥ 3 [10]. We provide a complementary result to this in our main theorem, which covers cases in which m ∤ n and solves a major portion of the problem.…”
mentioning
confidence: 82%
“…Still concerning cycles, there are many publications dealing with decompositions in which more than one cycle length occurs. In a very recent survey [24], Burgess, Danziger, and Traetta summarized the results of that kind and listed 62 reference items. In particular, Section 2.1.2 of that manuscript described a method based on the so-called "row-sum matrices", by which resolvable gregarious decompositions of K n * m and C n * m can be generated.…”
Section: A Survey On Gregarious Systemsmentioning
confidence: 99%
“…Let n > m ≥ 3 be odd integers with m ∤ n, and let g = gcd(m, n). We first prove a result that is a consequence of Theorem 2.5 and the following theorem, which is a special case of Theorem 1.4 of [13], taking t = 1, 2. We now apply Theorem 2.5 to obtain the following result.…”
Section: Constructing 2-factorizations Of Blown-up Cyclesmentioning
confidence: 99%
“…[13]). Let 1 ≤ m ′ < n ′ ≤ N be odd integers such that m ′ and n ′ are divisors of N. Then HWP(C g[N]; gm ′ , gn ′ ; α, β) has a solution whenever g ≥ 3, α + β = N and α, β = 1.…”
mentioning
confidence: 99%